Fe3O4@GO magnetic nanocomposites protect mesenchymal stem cells and promote osteogenic differentiation of rat bone marrow mesenchymal stem cells. (28th September 2020) - Zhang, He; Li, Sirong; Liu, Yufeng; Yu, Yijun; Lin, Shichao; Wang, Quan; Miao, Leiying; Wei, Hui; Sun, Weibin
Abstract : Fe3 O4 @GO/BMP2 protecting mesenchymal stem cells by regulating reactive oxygen species and promoting osteogenic differentiation of cells. Abstract : Fe3 O4 nanoparticles (Fe3 O4 NPs) are typical magnetic materials for bone tissue regeneration. However, the accompanying oxidative stress during the reaction process of Fe3 O4 NPs and H2 O2 in bone remodeling and disease may hinder their application. In order to reduce this side effect, we selected graphene oxide (GO) to modify Fe3 O4 NPs. We showed that Fe3 O4 @GO magnetic nanocomposites (Fe3 O4 @GO MNCs) eliminated 30% of H2 O2 in 3 h, and reduced the amount of ˙OH, the intermediate product of the Fenton reaction. The cellular study demonstrated that Fe3 O4 @GO MNCs reduced the cell damage caused by reactive oxygen species (ROS) and improved the activity of mesenchymal stem cells (MSCs). Moreover, when the magnetic field and bone morphogenetic protein-2 (BMP2) delivered by Fe3 O4 @GO MNCs worked together, osteogenic differentiation of MSCs in vitro was well promoted.